Short Communication: The existence of Javan Leopard (Panthera pardus melas Cuvier, 1809) in the non-conservation forest areas of Cisokan, Cianjur, West Java, Indonesia - SYA SYA SHANIDA; RUHYAT PARTASASMITA; TEGUH HUSODO; PARIKESIT PARIKESIT; PUPUT FEBRIANTO; ERRI NOVIAR MEGANTARA (Biodiversitas Journal of Biological Diversity, 2018)
Shanidah SS, Partasasmita P, Hudoso T. Parikesit, Febriato P, Meganatara EN. 2018. Short Communication: The existence of Javan Leopard (Panthera pardus melas Cuvier, 1809) in the non-conservation forest areas of Cisokan, Cianjur, West Java, Indonesia. Biodiversitas 19: 42-46. There is no accurate data about the number of individual leopards in Java Island in both conservation and non-conservation areas. In West Java, deforestation for plantations and agriculture is widespread, although it is unknown if leopard uses these human-altered habitats. Therefore, it is important to research the existence of leopards in Non-Conservation Forest Area (NCFA) in western Java, Indonesia. The aim of this research is to investigate: (i) evidence of leopard’s existence (ii) encounter rate of leopard’s existence; and (iii) estimation of individual leopards in NCFA, Cisokan, Cianjur, and West Java. Indirect data were obtained from sign surveys for feces, scrapes, footprints, and residual prey. We also obtained direct data with camera traps. We found 13 footprints, 2 feces, 4 scrapes, and 2 direct encounters by observers. The camera trap data recorded 12 independent leopard events and 8 leopard photos/100 trap days. Estimated number of leopards in Cisokan ranged 1-3 individuals.